Respuesta :
[tex]\\ \rm\Rrightarrow 5-3(2a+1)=-4+10[/tex]
[tex]\\ \rm\Rrightarrow 5-6a-3=6[/tex]
[tex]\\ \rm\Rrightarrow -6a+2=6[/tex]
[tex]\\ \rm\Rrightarrow -6a=6-2[/tex]
[tex]\\ \rm\Rrightarrow -6a=4[/tex]
[tex]\\ \rm\Rrightarrow a=\dfrac{4}{-6}[/tex]
[tex]\\ \rm\Rrightarrow a=\dfrac{2}{-3}[/tex]
Now
[tex]\\ \rm\Rrightarrow a+2[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{2}{-3}+2[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{2-6}{-3}[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{-4}{-3}[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{4}{3}[/tex]
Answer:
7/3
Step-by-step explanation:
5 - 3(2a+1) = -4 + 10
=> 5 - 6a + 3 = 6
=> 5 - 6 + 3 = 6a
=> 2 = 6a
=> 6a = 2
=> a = 2/6
=> a = 1/3
a + 2
1/3 + 2
=> 1/3 + 6/3
=> 7/3